Microencapsulation of probiotics and its applications with prebiotic in Pacific white shrimp larvae through Artemia sp. - Ramadhani, Dian Eka; Widanarni, Widanarni; Sukenda, Sukenda (Jurnal Akuakultur Indonesia, 2019)
ABSTRACTThis study aimed to produce microencapsulated probiotic Pseudoalteromonas piscicida (1Ub) and evaluate it with prebiotic mannan-oligosaccharide (MOS) through the enrichment of Artemia sp., on bacterial population, growth performances, immune responses, and disease resistance of Pacific white shrimp larvae. Microencapsulation of probiotic was done by the freeze-drying method. The shrimp larvae were reared for 13 days and fed by the Artemia sp. enriched with microcapsule of probiotic 1Ub (10 g/L), prebiotic MOS (12 mg/L), synbiotic, and control without administration of microencapsulated probiotic and prebiotic, including negative (C-) and positive (C+) control. On the day 14, all of the experimental shrimp larvae except C- were challenged through immersion method with Vibrio harveyi MR5339 (107 CFU/mL). This study showed that the administration of microcapsule of probiotic 1Ub, prebiotic MOS, and synbiotic through the enrichment of Artemia sp. could increase the bacteria population, growth performances, immune responses, and disease resistance of Pacific white shrimp larvae. Moreover, synbiotic treatment demonstrated the best result compared to other treatments.Keywords: probiotic, prebiotic, synbiotic, Pacific white shrimp, microencapsulation ABSTRAKPenelitian ini bertujuan untuk membuat mikrokapsul probiotik Pseudoalteromonas piscicida (1Ub) dan mengevaluasinya dengan prebiotik mannan-oligosaccharides (MOS) melalui pengayaan Artemia sp. terhadap populasi bakteri, performa pertumbuhan, respons imun dan resistensi penyakit pada larva udang vaname. Mikroenkapsulasi probiotik dilakukan dengan metode freeze-drying. Larva udang dipelihara selama 13 hari dan diberi pakan Artemia sp. yang telah diperkaya dengan mikrokapsul probiotik 1Ub (10 g/L), prebiotik MOS (12 mg/L), sinbiotik, dan kontrol tanpa penambahan mikrokapsul probiotik dan prebiotik, termasuk kontrol negatif (C-) dan positif (C+). Pada hari ke-14, seluruh larva udang percobaan kecuali C- diuji tantang melalui metode perendaman dengan Vibrio harveyi MR5339 (107 CFU/mL). Hasil penelitian menunjukkan bahwa pemberian mikrokapsul probiotik 1Ub, prebiotik MOS, dan sinbiotik melalui pengayaan Artemia sp. dapat meningkatkan populasi bakteri, performa pertumbuhan, respons imun, dan resistensi penyakit pada larva udang vaname. Selain itu, perlakuan sinbiotik menunjukkan hasil terbaik dibandingkan perlakukan lainnya.Kata kunci : probiotik, prebiotik, sinbiotik, udang vaname, mikroenkapsulasi